Relevansi Prinsip Kesopanan Leech dengan Pendidikan Karakter pada Tuturan Guru dalam Interaksi Pembelajaran Siswa Usia Dini - Rahmawati, Fithriyah; Luthfatun Nisa' (Institut Agama Islam Negeri Madura, 2024)
This research aims to discuss the extent to which politeness strategies are applied by teachers and students in classroom interactions and to analyze the types of politeness maxims based on the theory proposed by Geoffrey Leech. The method used in this research is qualitative with a descriptive approach. The research subjects involved are 1st-grade elementary school students, educators, educational staff, and parents of students at SDI Al Uswah Pamekasan. The findings of this research consist of the distribution of maxims analyzed based on Leech's politeness principles theory, with the percentage of usage of politeness principles and the 6 maxims of the politeness principle of tact ranking highest in their usage in conversations between teachers and students during the course of learning. The six maxims proposed by Leech include the maxim of tact, the maxim of generosity, the maxim of praise, the maxim of modesty, the maxim of agreement, and the maxim of sympathy. The conclusion of this research is that each maxim proposed by Leech can be found in the interaction process between teachers and students, with language delivery based on the principle of politeness.